1999
DOI: 10.1024/0301-1526.28.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Veränderungen der extrazellulären Matrix in der varikösen Venenwand

Abstract: All varices exhibited an increased expression pattern in comparison to healthy veins. The venous vessel wall was often non-homogeneously enlarged. The intima was always more involved than the media and showed enhanced accumulation, whereas, the adventitia was not influenced by the pathological process. Collagen IV exhibited an early accumulation, especially in the subendothelial region. The other matrix proteins demonstrated an increase in fibre propagation parallel to the enlargement of the vessel wall. Essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Indirect biochemical studies have demonstrated a decrease in the elastin content of the affected vein wall [8, 9, 17, 18, 19, 20, 21]. Recently Kirsch et al [22], who examined the structure and arrangement of elastic fibers in the varicose condition, found an increase in these during the initial stages of disease. However, as disease progressed, a reduction and fragmentation of fibers was observed, thus explaining the rigidity of the varicose vein wall compared to the walls of healthy veins.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect biochemical studies have demonstrated a decrease in the elastin content of the affected vein wall [8, 9, 17, 18, 19, 20, 21]. Recently Kirsch et al [22], who examined the structure and arrangement of elastic fibers in the varicose condition, found an increase in these during the initial stages of disease. However, as disease progressed, a reduction and fragmentation of fibers was observed, thus explaining the rigidity of the varicose vein wall compared to the walls of healthy veins.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal wall structure of varicose veins, with increased fiber propagation parallel to the enlargement of the vessel wall, decreased mechanical properties, and variations in lumen diameter, can lead to hemodynamic disturbance, turbulence, aneurysm development, and increased long-term risk of thrombosis, embolization, and rupture when exposed to arterial pressure. 16,17 Even long-term functioning normal vein grafts have been found to be at significant risk of aneurysmal degeneration. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, collagen fibrils enter the area between the muscle fibers in the media layer, thereby disturbing the circular order of muscles (19,20). There is a decrease in the elastin fibers (10,18,21) and a fragmentation in the internal elastic lamina (13,18,20). However, there is an increase in other matrix proteins fibronectin, laminin and tenascin (18).…”
Section: Introductionmentioning
confidence: 98%
“…Although there are findings that show a decreased amount of collagen (7,8), the amount of collagen generally increases (9)(10)(11)(12)(13)(14)(15) and this situation is even observed in cellular cultures (15)(16)(17). The increase in collagen occurs both in the intima (13) and in the media (12,18). Furthermore, collagen fibrils enter the area between the muscle fibers in the media layer, thereby disturbing the circular order of muscles (19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation